Determination of Five Heavy Metal Ions in Environmental Samples by a Rapid High-Performance Liquid Chromatography - WU, XIANHUA; LI, MING; LIN, HONG; HU, QIUFEN; YANG, GUANGYU (Asian Journal of Chemistry, 2010)
A new method for the simultaneous determination of five heavy metal ions in water and food by a rapid high-performance liquid chromatography was developed. The lead, cadmium, mercury, nickel and zinc ions were pre-column derivatized with 2-(2-quinolinylazo)-resorcin (QAR) to form coloured chelates, then the Pb-QAR, Cd-QAR, Hg-QAR, Ni-QAR and Zn-QAR chelates were enriched by solid phase extraction with CI8 cartridge. The enrichment factor of 100 was achieved by eluting the retained chelates from the cartridge with tetrahydrofuran. These chelates were separated on a Zorbax stable bound rapid analysis column (4.6 x 50 mm, 1.8μm) with 65% methanol (containing 0.05 mol/L of pH = 8.5 pyrrolidine-acetic acid buffer salt and 0.01 mol/L of CTMAB) as mobile phase at a flow rate of 2.0 mL/min and detected with a photodiode array detector from 450-600 nm. The Pb-QAR, Cd-QAR, Hg-QAR, Ni-QAR and Zn-QAR chelates were separated completely within 2.0 min. The detection limits of lead, cadmium, mercury, nickel and zinc are 1.5, 1.2, 1.0, 1.8 and 2.0 ng/L, respectively in the original samples. This method was applied to the determination of the five metal ions in water and food samples with good results.